Interactions between major chlorogenic acid isomers and chemical changes in coffee brew that affect antioxidant activities. (15th December 2016) - Liang, Ningjian; Xue, Wei; Kennepohl, Pierre; Kitts, David D.
Graphical abstract: Highlights: Roasting contribute more to changes in CGA content than geographical factor. Browning parameters corresponded highest to TEMPO scavenging capacity. CGA content corresponded highest to intracellular antioxidant activity. Abstract: Coffee bean source and roasting conditions significantly ( p  < 0.05) affected the content of chlorogenic acid (CGA) isomers, several indices of browning and subsequent antioxidant values. Principal component analysis was used to interpret the correlations between physiochemical and antioxidant parameters of coffee. CGA isomer content was positively correlated ( p  < 0.001) to capacity of coffee to reduce nitric oxide and scavenge Frémy's salt. Indices of browning in roasted coffee were positively correlated ( p  < 0.001) to ABTS and TEMPO radical scavenging capacity, respectively. Only the CGA content of coffee corresponded to intracellular antioxidant capacity measured in Caco-2 intestinal cells. This study concluded that the intracellular antioxidant capacity that best describes potential health benefits of coffee positively corresponds best with CGA content.